Tajik Persian Readings in History, Culture and Society - Ahmad, Razi (Open textbook library., 2016)
Tajik Persian: Readings in History, Culture and Society seeks to help students develop reading proficiency in Tajik at advanced level through authentic texts written for native speakers and provides them glimpses into the history, culture and society of Tajikistan without losing its focus on cultural aspects of the country—an aspect that constitutes a core component in the second language acquisition. The book can be adopted by instructors as a supplementary or the main textbook for advanced-level courses.